Leukocyte Esterase Activity in Vaginal Fluid of Pregnant and Non-Pregnant Women With Vaginitis/Vaginosis and in Controls - Per-Anders Mårdh; Natalia Novikova; Ola Niklasson; Zoltan Bekassy; Lennart Skude (Hindawi Limited, 2003)
Objectives: To determine the leukocyte esterase (LE) activity in vaginal lavage fluid of women with acute and recurrent vulvovaginal candidosis (VVC and RVVC respectively), bacterial vaginosis (BV), and in pregnant and non-pregnant women without evidence of the three conditions. Also to compare the result of LE tests in women consulting at different weeks in the cycle and trimesters of pregnancy.The LE activity was correlated to vaginal pH, number of inflammatory cells in stained vaginal smears, type of predominating vaginal bacteria and presence of yeast morphotypes.